A longitudinal study of autoantibodies against cytochrome P450 side-chain cleavage enzyme in dogs (Canis lupus familiaris) affected with hypoadrenocorticism (Addison's disease) - Boag, Alisdair M.; Christie, Michael R.; McLaughlin, Kerry A.; Syme, Harriet M.; Graham, Peter; Catchpole, Brian (Elsevier, 2018)
Autoantibodies directed against the P450 side chain cleavage enzyme (P450scc) have been recently described in dogs affected with hypoadrenocorticism, consistent with an immune-mediated pathogenesis of this endocrinopathy. In human autoimmune Addison’s disease, autoantibodies may have a predictive value, being detectable before clinical signs developing, and have been shown to persist for a period of time after diagnosis. Furthermore, an autoantibody positive status post-diagnosis has been associated with successful remission of Addison’s disease following B-cell depletion, suggesting active immunopathology in these cases. The current study was designed to investigate changes in serum P450scc autoantibody status over time in dogs diagnosed with spontaneous hypoadrenocorticism. P450scc autoantibodies were measured using a species-specific radioimmunoprecipitation assay in an initial cohort of 213 dogs, indicating a prevalence of 24%. Thirty two of these dogs had repeat samples (n = 80 in total) available for analysis. Five dogs were consistently P450scc autoantibody positive in all samples, for up to 425 days following first sampling. Three dogs were initially autoantibody positive, then became seronegative at later time points. One dog, a 1 year old female entire standard poodle, was initially negative for P450scc autoantibodies, but seroconverted 18 months after diagnosis. The remaining 23 dogs with multiple samples available were consistently P450scc autoantibody negative. Persistence was not associated with sex (p = 0.673). This study demonstrates persistence of P450scc autoantibodies in a subset of dogs affected with hypoadrenocorticism and seroconversion over one year post-diagnosis. P450scc autoantibody reactivity in human autoimmune Addison’s disease has been associated with sex, with females having a higher prevalence, possibly due to P450scc expression in the ovary acting as an additional source of antigenic stimulation. However, there was no sex difference in autoantibody persistence in the dogs affected with hypoadrenocorticism. Autontibody persistence in dogs with hypoadrenocorticism might represent persistent pathology, due to residual antigenic stimulation and autoimmune inflammation in the adrenal gland.